2018
DOI: 10.2334/josnusd.17-0390
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT observation of <i>in vivo</i> temporal change in mandibular condyle morphology in <i>BMAL1</i> knockout mice

Abstract: Brain and muscle Arnt-like protein-1 (BMAL1) knockout mice exhibit accelerated aging, abnormal glucose metabolism, and impaired adipocyte differentiation, among other phenotypes, which are effects associated with the BMAL1 gene. No study has investigated temporal changes in the deformation of the mandibular condyle and the presence of calcification in areas surrounding the mandibular condyle. In a study of 12 C57/BL strain mice under inhalation anesthesia, we collected images of the mandibular condyle at 6 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Thus, 36-week-old mice can be considered to be in early middle-age and do not normally show abnormal decreases in BMD. In the BMAL1-KO mice, normal growth is observed until about 11 weeks, and then pathological changes in some biological functions, such as activity levels and body weight, gradually develop [17]. Zhou et al [13] evaluated the morphology and bone volume of the mandibular condyle in BMAL1-KO mice and showed that no significant hypoplasia or low bone volume was evident until at least 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 36-week-old mice can be considered to be in early middle-age and do not normally show abnormal decreases in BMD. In the BMAL1-KO mice, normal growth is observed until about 11 weeks, and then pathological changes in some biological functions, such as activity levels and body weight, gradually develop [17]. Zhou et al [13] evaluated the morphology and bone volume of the mandibular condyle in BMAL1-KO mice and showed that no significant hypoplasia or low bone volume was evident until at least 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The low-bone-mass phenotype was recapitulated in MSCs with conditional Bmal1 knockout (Bmal1 f/f .Prx1-cre) 45) . Abnormal mandibular condyle morphology 46) and mandibular hypoplasia 47) were also demonstrated in Bmal1 knockout mice.…”
Section: Adult Stem Cellsmentioning
confidence: 92%
“…Major clock genes, Bmal1 and Per2 , were oscillating in a regular 24-hour circadian rhythm in tooth-derived stem cells, suggesting that Bmal1 and Per2 may be regulators of tooth development ( Furukawa et al, 2005 ; Hilbert et al, 2019 ; Jiang et al, 2022 ; Lacruz et al, 2012 ; Zheng et al, 2013 ). The role of Bmal1 in promoting oral and maxillofacial development has been previously investigated ( Hirai et al, 2018 ; Koshi et al, 2020 ; Liu et al, 2022 ; Zhao et al, 2018 ). In particular, Bmal1 was recently found to regulate dental pulp cell differentiation and dentin formation ( Xu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%